Kaurna' Warra : a selected wordlist from the language of the Kaurna people of the Adelaide Plains - Fitzpatrick, Philip, 1948-; South Australia. Aboriginal Heritage Branch ([Adelaide] : Aboriginal Heritage Branch, Dept. of Environment and Planning, 1991)
Kaurna-English, English-Kaurna wordlists.
First published: 1989.
Bibliography: pages 38-39.
Keywords: Aboriginal Australians -- South Australia -- Languages; Aboriginal Australians -- South Australia -- Adelaide Plains -- Languages; Kaurna language -- Glossaries, vocabularies, etc; Kaurna (Australian people); Kaurna language; Adelaide (SE SA SI54-09); Australian